Correction: Activating the lattice oxygen in (Bi0.5Co0.5)2O3 by vacancy modulation for efficient electrochemical water oxidation. Issue 8 (8th February 2021) - Liu, Huan; Li, Xiaoning; Peng, Cailing; Zhu, Liuyang; Zhang, Yuanxi; Cheng, Huiru; Cui, Jiameng; Wu, Qingmei; Zhang, Yingying; Chen, Zezhi; Zou, Wei; Gu, Wen; et al.
Abstract : Correction for 'Activating the lattice oxygen in (Bi0.5 Co0.5 )2 O3 by vacancy modulation for efficient electrochemical water oxidation' by Huan Liu et al., J. Mater. Chem. A, 2020, 8, 13150–13159, DOI: ; 10.1039/D0TA03411H .